2022
DOI: 10.1109/access.2022.3188306
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure-Based Pedestrian Risk Tagging Methodology to Support AV Risk Assessment

Abstract: This work is sponsored in part by Ignition Grant from Singapore Institute of Technology and kind support from the UofG-SIT Scholarship Ph.D. Scholarship for the 1st Author. We are thankful to MooVita Pte Ltd for their collaboration in exploring this concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Yet, a recent review paper found that there have been extraordinarily few studies of the potential to transport dangerous goods by aircraft [50]. The literature mainly covered risk assessment [51], traffic flow prediction [52], vehicle routing [53], tour length optimization [54], facility locating, scheduling, aircraft loading [55], emergency response [56], and accident cause analysis [40].…”
Section: Transporting Dangerous Goodsmentioning
confidence: 99%
“…Yet, a recent review paper found that there have been extraordinarily few studies of the potential to transport dangerous goods by aircraft [50]. The literature mainly covered risk assessment [51], traffic flow prediction [52], vehicle routing [53], tour length optimization [54], facility locating, scheduling, aircraft loading [55], emergency response [56], and accident cause analysis [40].…”
Section: Transporting Dangerous Goodsmentioning
confidence: 99%